SHARIA COMPLIANCE CHALLENGES IN THE ISLAMIC PAWNSHOP INDUSTRY: A STUDY OF RAHN-BASED FINANCIAL SERVICES - Nasrullah Bin Sapa; Rahman Ambo Masse; Muhammad Majdy Amiruddin (Academic Bright Collaboration, 2026)
This study aims to critically examine the Sharia compliance challenges in the Islamic pawnshop industry in Indonesia, particularly within Rahn-based financial services. It focuses on key issues such as contract structuring, fee (ujrah) determination, collateral management, governance effectiveness, regulatory implementation, and customer-related factors influencing compliance. The research employs a qualitative descriptive approach combined with normative legal analysis and supported by limited quantitative surveys. Data were collected through in-depth interviews, direct observations, and document analysis of DSN-MUI fatwas, regulatory frameworks, standard operating procedures, contracts, and financial reports. Additionally, stakeholder perspectives were gathered through questionnaires involving management, operational staff, Sharia Supervisory Board members, regulators, and customers. A case study was also conducted at an Islamic pawnshop institution in Makassar to provide contextual insights. The findings reveal that the implementation of Rahn and Ijarah contracts in Islamic pawnshops generally complies with DSN-MUI Fatwas, particularly No. 25/2002, No. 26/2002, and No. 92/2014, and successfully avoids explicit elements of riba. However, several critical challenges persist. These include the improper calculation of administrative and storage fees based on loan value rather than actual costs, which potentially introduces elements of riba. Furthermore, the use of multi-contract schemes (e.g., Qardh–Ijarah combinations) creates ambiguity and raises concerns regarding prohibited hybrid contracts. Issues of gharar are also identified in certain pricing and discounting practices. Additional challenges include inconsistencies in collateral management, uneven effectiveness of Sharia governance, and limited staff competency. From the demand side, while customer religiosity supports the adoption of Islamic pawnshop services, low levels of Sharia financial literacy contribute to information asymmetry, potentially masking non-compliance and affecting trust and satisfaction. This study highlights the need for strengthening Sharia governance frameworks, including more rigorous auditing and monitoring mechanisms. It underscores the importance of implementing cost-based ujrah calculations, enhancing regulatory clarity on multi-contract structures, and improving transparency in pricing and disclosure practices. Furthermore, capacity-building programs for staff and systematic efforts to improve public literacy in Islamic finance are essential to ensure sustainable compliance. Policymakers and regulators are also encouraged to develop standardized compliance metrics and enforce more consistent supervision across the industry. This research offers a comprehensive and integrative analysis of Sharia compliance challenges in the Islamic pawnshop sector by combining legal, operational, and behavioral perspectives. It contributes to the literature by bridging the gap between normative Sharia principles and practical implementation, particularly in the context of Rahn-based financial services in Indonesia, and provides actionable insights for enhancing both compliance and institutional credibility.